American Health Dilemma : a Medical History of African Americans and the Problem of. - Byrd, W. Michael (Routledge, 2000)
Beginning with the origins of Western medicine and science in the ancient world the authors explore the relationship between race, medicine and health care and apply their findings to the African American experience through history.